1558. Commensal Neisseria Species as a Cause of Disease in Patients Taking Eculizumab. (26th November 2018) - Crew, Page; McNamara, Lucy; Waldron, Peter; McCulley, Lynda; Jones, S Christopher; Bersoff-Matcha, Susan
Abstract: Background: Non-meningococcal and nongonococcal Neisseria spp. are usually commensal and rarely cause invasive disease in humans. Eculizumab, a terminal complement inhibitor, increases susceptibility to meningococcal disease, but data on atypical Neisseria spp. disease in persons receiving eculizumab are lacking. This case series describes postmarketing reports of disease by commensal Neisseria spp. in patients receiving eculizumab. Methods: The FDA Adverse Event Reporting System (FAERS) database and the medical literature were searched for cases of disease by any nonmeningococcal and nongonococcal Neisseria spp. in patients receiving eculizumab. Included cases had a diagnosis of disease by any atypical Neisseria spp. with onset on or before January 31, 2018 and ≥1 dose of eculizumab in the 3 months prior to disease. Results: The search identified seven FAERS cases, including one case also reported in the literature. Patient ages ranged from 4 to 38 years. Five patients had positive blood cultures, of which three had an indwelling catheter for vascular access ( n = 2, N. sicca/subflava ) or hemodialysis ( n = 1, N. cinerea ). Two patients with bacteremia had N. cinerea septic shock with possible cholecystitis, and N. mucosa sepsis with concurrent Streptococcus bacteremia after gastroenteritis. The remaining two cases in the series included one with N. sicca bacterial peritonitis associated with a peritoneal dialysis catheter (negative blood cultures, other cultures not specified), and one with a diagnosis of N. flavescens sepsis while neutropenic (specimen source not specified). All seven patients were hospitalized and three had sepsis or septic shock. All cases resolved with antibiotics and supportive care. Conclusion: We identified seven cases of serious disease caused by atypical Neisseria spp. among eculizumab recipients. Since these organisms are typical inhabitants of the oropharynx and urogenital tract and are not skin flora, the source of disease was unclear. Our data suggest that eculizumab may confer increased risk for disease by usually commensal Neisseria spp. Healthcare professionals are encouraged to treat all Neisseria spp. isolated from sterile sites as pathogenic, and not as contaminants, in patients receiving eculizumab. Disclosures: All authors: No reported disclosures.